Influence of Cu:Fe ratio in synthesis of higher alcohols from syngas over CuFeCoK/attapulgite catalysts - Aho, Atte; Lind, Noora; Virtanen, Pasi; Mäki-Arvela, Päivi; Eränen, Kari; Granroth, Sari; Korpelin, Ville; Honkala, Karoliina; Russo, Vincenzo; Simakova, Irina; Murzin, Dmitry Yu. (Elsevier, 2025)
Synthesis of higher alcohols from syngas (H2:CO ratio 2 and 1) was performed at 225–300 °C and 30 bar over copper, iron and cobalt containing catalysts supported on attapulgite and promoted with potassium. The Cu:Fe ratio was varied to study its influence on the syngas conversion and product distribution. It was found that while the copper rich catalyst 17Cu3FeCoK/attapulgite resulted in higher selectivity to the undesired alkanes with methane as the major one, the iron rich 3Cu17FeCoK/attapulgite was more selective towards alkenes. Selectivity to CO2 was independent on the Cu:Fe ratio tested in this work. With the higher H2:CO ratio (i.e. 2) selectivity to the liquid products increased with the increasing iron content. Moreover, a higher iron content in the catalyst improved formation of higher alcohols while the α-value reflecting the chain growth probability was more or less independent on the catalyst type.